PROFESSIONAL DEVELOPMENT: ENGLISH TEACHERS’ PERCEPTION - Bagas Bagas (Graduate Program, University of Islam Malang, 2020)
The research aims to: 1) explore the description of perception of English teachers in SMAN 1 Karangrejo on the professional development, 2) describe the English teachers ‟perception on their professionalism after taking professional development, and 3) describe English teachers ‟professionalism after taking professional development.The research was conducted in SMAN 1 Karangrejo Tulungagung. The subject of this reserach are three English teachers at the school. The research uses qualitative method research in the form of case study. The researcher used interview, observation, and document analysis as the strategy for collecting data.The results are: 1) all the three teachers in this research had been taking professional development before. They all agreed to the idea that professional development was an ongoing process to teach in the classroom according to the lesson plan, 2) conducting professional development supplied a lot of advantages for the three teachers. They thought that professional development brought some improvements in teachers’ professionalism. They were able to develop students’ thinking and communication skill, to manage the class, and to enrich teaching techniques, and 3) the teachers acknowledged that conducting professional development gave massive benefits for them, especially in improving their qualities as good English teachers. Keywords: professional development, perception